Effect of Cathode Distance, Anode and Electroplating Time on Aluminum Alloy Corrosion Rate - Agus Dwi Putra; Dewi Izzatus Tsamroh; Yayi Febdia Pradani; Ratna Fajarwati Meditama; Ahmad Muflih (TRANSMISI, 2023)
Aluminum foil is used more often than actual aluminum in everyday life because aluminum is actually quite unstable and is not suitable for securing heavy containing objects. For car wheels, aluminum is mixed with manganese and then hardened to withstand the load. Using aluminum alloys requires an electroplating process to increase corrosion resistance, decorative value and friction resistance. The purpose of this study was to determine the properties of anodized cathode aluminum alloy and the required coating time. In this study, a quantitative experiment used 20 samples. The results showed that there were defects in the aluminum alloy lattice, but not too significant. Different corrosion rate values were shown using electrolysis periods of 30 minutes and 60 minutes combined with anode-cathode distances of 5 cm, 10 cm and 15 cm. The group with 30 minutes of coating time and 5 cm anode-cathode distance had the highest corrosion rate (0.853 mm/year), while the group with 30 minutes of coating time and 10 cm anode-cathode distance had the lowest corrosion rate (0.610). The group with 60 minutes of coating time and 10 cm distance between the anode and cathode had the highest corrosion rate of 1,564 mm/year, while the group with 60 minutes of coating time and 15 cm distance had the lowest corrosion rate. The anode-cathode distance partially affects the corrosion rate of aluminum alloy electroplating. The smaller the distance between the anode and cathode, the higher the corrosion rate of the aluminum alloy. The longer the coating lasts, the higher the corrosive rate of the Al alloy.